2012
DOI: 10.1534/genetics.112.143248
|View full text |Cite
|
Sign up to set email alerts
|

NAT1/DAP5/p97 and Atypical Translational Control in the Drosophila Circadian Oscillator

Abstract: Circadian rhythms are driven by gene expression feedback loops in metazoans. Based on the success of genetic screens for circadian mutants in Drosophila melanogaster, we undertook a targeted RNAi screen to study the impact of translation control genes on circadian locomotor activity rhythms in flies. Knockdown of vital translation factors in timeless protein-positive circadian neurons caused a range of effects including lethality. Knockdown of the atypical translation factor NAT1 had the strongest effect and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
26
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 65 publications
3
26
0
Order By: Relevance
“…They support the emerging notion that translational control is critical for the function of circadian pacemaker neurons (8, 9). Our results also emphasize that ATX2 can function as a translational activator, as well as a translational repressor (1214).…”
supporting
confidence: 75%
“…They support the emerging notion that translational control is critical for the function of circadian pacemaker neurons (8, 9). Our results also emphasize that ATX2 can function as a translational activator, as well as a translational repressor (1214).…”
supporting
confidence: 75%
“…Considering previous reports showing that the 3 ′ UTR can also contribute to cap-independent translation (Izquierdo and Cuezva 2000;Martinez-Salas et al 2008;Bradley et al 2012;Bukhari et al 2016;Weingarten-Gabbay et al 2016), IRESs or elements that affect IRES activity may have been missed in this screen. Future screens can be conducted to include the 3 ′ UTR in the reporter plasmids and expand the number of targets assayed.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have reported the roles of the eIF4E and its binding proteins in circadian clock physiology. For example, knockdown of the eIF4G homolog, NAT1, significantly reduces PER expression and lengthens the behavioral period in Drosophila (Bradley et al, 2012). Moreover, a recent study reported that the clock coordinates ribosomal biogenesis in the liver by rhythmic activation of the mTOR/4E-BP1/eIF4E pathway (Jouffe et al, 2013).…”
Section: Discussionmentioning
confidence: 99%